L-CITRULLINE AS A NATURAL ERGOGENIC SUPPLEMENT: A COMPREHENSIVE LITERATURE REVIEW OF ITS EFFECTS IN NITROGEN METABOLISM AND HUMAN PERFORMANCE - Maciej Ficek; Wojciech Gawęda; Wiktoria Łobodzińska; Zuzanna Hamouta; Justyna Adamczyk (International Journal of Innovative Technologies in Social Science, 2025)
Purpose: This study aims to provide a comprehensive examination of the role of L-citrulline in human physiology, with a particular focus on nitrogen metabolism and its potential applications in sports and exercise science. L-citrulline, a non-essential amino acid synthesized endogenously, participates in the urea cycle where it contributes to the detoxification of ammonia, a byproduct of protein catabolism. In addition, it plays an important role in the nitric oxide (NO) pathway, thereby influencing vascular tone and blood flow regulation. These biochemical functions have attracted considerable scientific attention, as they may translate into practical benefits for physical performance and recovery. Specifically, L-citrulline supplementation has been investigated for its ability to enhance exercise capacity, support training adaptation, reduce muscle soreness, and improve post-exercise recovery. Furthermore, there is growing interest in its potential to delay fatigue by improving oxygen delivery and nutrient utilization during strenuous activity. Beyond performance outcomes, the safety profile of L-citrulline has also been evaluated, with current evidence suggesting that it is well tolerated when consumed at doses commonly used in clinical and sports settings. Taken together, these factors highlight the multifaceted relevance of L-citrulline as both a physiological substrate and a promising ergogenic aid. Methodology: A systematic review of scientific articles was conducted, focusing on studies related to the ergogenic effects of L-citrulline. The review mainly includes clinical trials, meta-analyses, and research on various populations. Findings: Regular L-citrulline supplementation appears to enhance NO production, improve vasodilation, and facilitate ammonia clearance, which collectively support endurance and strength performance. The review suggests that L-citrulline also reducing muscle soreness, improving recovery, delaying fatigue, although effects vary by dose, training status, sex, and the long-term safety of regular use. Synergistic effects have been noted when L-citrulline is combined with other supplements like malate or BPFG. Conclusions: Current evidence supports the potential of regular L-citrulline supplementation as an metabolic enhancer. However, further research is warranted to elucidate its precise role in broader aspects of metabolic health and to determine optimal dosing strategies. These remain important areas for future investigation.